2006
DOI: 10.1080/15389580500412994
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index (BMI) as a First-Line Screening Criterion for Detection of Excessive Daytime Sleepiness Among Professional Drivers

Abstract: Obese drivers with BMI above 32 are highly prone to be sleepy during the day. Their subjective reports of OSA or fatigue symptoms are not reliable. Therefore it is highly recommended to screen them easily by weight and height measure for further sleep study and decision about their driving abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 36 publications
4
50
2
7
Order By: Relevance
“…(10) Therefore, it could be postulated that the tendency toward excessive daytime sleepiness can be predicted, to some extent, by BMI. (11) In addition, various studies have found an association between degree of OSAS severity and obesity. (12,13) Other risk factors, such as gender, age, alcohol consumption and smoking, are well known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) Therefore, it could be postulated that the tendency toward excessive daytime sleepiness can be predicted, to some extent, by BMI. (11) In addition, various studies have found an association between degree of OSAS severity and obesity. (12,13) Other risk factors, such as gender, age, alcohol consumption and smoking, are well known.…”
Section: Introductionmentioning
confidence: 99%
“…(17) The relevance of studies of OSAS in truck drivers is related to the inability of such individuals to maintain a satisfactory level of concentration and the necessary psychomotor coordination to drive, (1) which increases the risk of accidents. (11,(19)(20)(21) The decrease in the performance of drivers has been observed by various researchers. (19,21,22) In view of what has been presented above, the objective of the present study was to determine the prevalence of and identify factors associated with OSAS in a population of truck drivers.…”
mentioning
confidence: 99%
“…Já em outra pesquisa com 153 motoristas comerciais israelenses, 77,7% tinham SAOS, 47,1% estavam sonolentos, 19% tinham sonolência severa e 28,1% sonolência moderada 18 .…”
Section: Aspectos Epidemiológicos Dos Transtornos Do Sonounclassified
“…Ambos estão associados independentemente a problemas de saúde (distúrbios endócrinos, Hipertensão Arterial Sistêmica e ronco) 7 . Motoristas obesos tinham maiores índices de sonolência excessiva diurna 6,19 , apnéia do sono 16 e SAOS 14,18,20,24 .…”
Section: Obesidadeunclassified
See 1 more Smart Citation